Reasons for the internationalisation and performance of technology-based firms: building an institutional support agenda - García Cabrera, Antonia Mercedes (2020)
Technology-based firms (TBFs) must constantly invest in R&D&I activities in order to be competitive. The recovery of this investment is a priority to ensure the continuity of the business project. Sometimes this is only possible if the company extends the scope of its activity by entering international markets. However, many TBFs do not undertake this type of expansion, neither reap negative results in doing so. In this context, this paper aims to analyse the reasons that lead TBFs to internationalise and their impact on the results. The hypotheses formulated where tested empirically, through parametric and non-parametric statistical techniques, applied to a group of TBFs’ founders and managers in Spain, consulted at two moments in time ―2009 (175 firms) and 2016 (53 of the 175 previous firms). The results show that: 1) internationalised TBFs achieve better results than noninternationalised TBFs in terms of operating income and ordinary results; 2) the reasons that drive TBF managers to undertake internationalisation seem to be more relevant in the adoption of this decision when they are offensive than when they are defensive; and 3) the decision to internationalise adopted for offensive reasons is associated with higher operating income and/or ordinary results for the TBF, while the decision made for defensive reasons is associated with lower economic profitability for the company. These results are useful for building an institutional support agenda for the internationalisation of TBFs.